Synthesis of copper nanowires and its application as transparent conducting electrode - Tan, Michael R.; Balela, Mary Donnabelle L. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Bulk copper (Cu) is one of the most abundant metals found in the earth's crust. It can easily be extracted and efficiently recovered from end-of-life products which makes it inexpensive. Cu is also an excellent electrical and thermal conductor. This makes Cu suitable for low value commercial applications such as electrical transmission wires and coin plating. However, the abundance of Cu coupled with its excellent conductivity makes it a very viable alternative to replace more expensive materials in the electronics industry. In particular, electrodes made from Cu nanowires are widely studied as a possible replacement to expensive indium tin oxide (ITO). ITO is commonly used as a layer on various devices with touch screen technology such as OLEOs, photovoltaics, and various sensors. Many of the current research on Cu nanowires have focused on the optimization of solution parameters and morphological control. There are only a few mechanistic studies possibly due to complex electrochemical and/or chemical reactions occurring simultaneously in the solution. Electrochemical measurements that could provide an insight on how different experimental factors, such as pH, temperature, and concentration, affect the morphology and composition of the resulting Cu products are limited. In this work, we present a simple preparation method for Cu nanowires by electroless deposition and hydrothermal reaction in aqueous solution. Cu nanowires were successfully grown through a low temperature electroless deposition on aqueous solution for 1 h. Ethylene diamine (EDA) was utilized to promote anisotropic reduction of Cu(II) by hydrazine. Cu nanowires with mean diameters around 90 nm and lengths exceeding 50 μm were synthesized using 171 mM EDA at 60°C, giving an effective aspect ratio of about 450. Without EDA, nanoparticle growth is observed. The synthesis temperature was also significant in limiting nanoparticle formation. Decreasing the temperature resulted to 1 dimensional growth and fewer nanoparticles. In situ monitoring of redox potential, in conjunction with thermodynamic calculations, was performed to elucidate the formation of Cu nanowire in solution. On the other hand, longer and thinner Cu nanowires were produced through hydrothelmal synthesis using oleylamine, oleic acid, and Cl- ions as coordinating agents. Cu nanowires with mean diameters around 82.3 nm and lengths exceeding 300 μm were synthesized using 2 % vol. oleylamine and 1.8 mM oleic acid at 120°C after 12 h. The Cu nanowires exhibit twinning and growth along the 110 direction. Without Cl-, octahedral crystals instead of nanowires were formed. The addition of oleic acid as coordinating agent resulted to fewer particles and smoother nanowires which exhibit excellent mechanical stability. A transparent conducting electrode was made from Cu nanowire ink-coated glass substrate. The sheet resistance the Cu nanowire glass electrode was measured to be about 9617 Ω sq-1 at 84.5% transparency for 30.3 μg/cm-2 of Cu nanowires coated on a 1x1 in glass. This decreases to about 197 Ω sq-1 at 61 % transparency as the number of coatings was increased to 151.5 μg/cm-2. Finally, a 5 mA LED was powered in a series connection using the Cu nanowire glass electrode in order to prove its viability
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman
Keywords: Copper; Nanowires; Nanostructured materials